Regioisomeric wide-band-gap polymers with different fluorine topologies for non-fullerene organic solar cells. Issue 3 (13th December 2018) - Li, Yuxiang; Lee, Jin-Woo; Kim, Minseok; Lee, Changyeon; Lee, Young Woong; Kim, Bumjoon J.; Woo, Han Young
Abstract : The effects of different fluorine substituent topologies on the morphological and photovoltaic properties are studied for two regioisomeric donor polymer-based nonfullerene organic solar cells. Abstract : Two regioisomeric wide-band-gap donor polymers with different fluorine topologies are designed and synthesized for use in nonfullerene organic solar cells (NFOSCs). Two fluorine atoms are substituted on the phenylene moiety in an anti (PTBDD2F-a) or a syn (PTBDD2F-s) fashion. The two isomeric polymers show nearly identical optical, thermal, and electrochemical properties, but exhibit different interchain packing and film morphologies in both pristine and blend films with an n-type acceptor (ITIC). These different morphological properties are related to differences in the molecular dipole, symmetry, and backbone curvatures of PTBDD2F-a and PTBDD2F-s, which influence the interchain packing and resulting electrical properties. From grazing incidence X-ray scattering measurements, PTBDD2F-a:ITIC shows more pronounced and two separate out-of-plane (010) peaks compared to PTBDD2F-s:ITIC, suggesting a stronger face-on cofacial packing of ITIC molecules in the PTBDD2F-a:ITIC blend. A higher domain purity (1.00 vs . 0.71) is also observed for PTBDD2F-a:ITIC compared to PTBDD2F-s:ITIC in the resonant soft X-ray scattering measurements. These different morphological features induce ∼2.5 times higher hole mobility and ∼6 times higher electron mobility with higher power conversion efficiency (6.60 vs. 5.47%) for PTBDD2F-a:ITIC than for PTBDD2F-s:ITIC. This comparative study highlights the effects of different fluorine topologies along the polymer backbone, which should be carefully considered to optimize the blend morphology and optoelectronic properties of NFOSCs.